Cystic Craniopharyngiomas: Microsurgical or Stereotactic Treatment?. Issue 5 (May 2017) - Rachinger, Walter; Oehlschlaegel, Florian; Kunz, Mathias; Fuetsch, Manuel; Schichor, Christian; Thurau, Stephan; Schopohl, Jochen; Seelos, Klaus; Tonn, Jörg‐Christian; Kreth, Friedrich‐Wilhelm
Abstract : BACKGROUND: : Prognosis and treatment of cystic craniopharyngiomas are poorly defined. OBJECTIVE: : To analyze progression‐free survival (PFS) and safety profile of cystic craniopharyngiomas undergoing resection or minimally invasive drainage procedures. We compared further outcome measurements for cystic and solid tumors undergoing resection to elucidate the impact of the initial tumor composition on both PFS and the toxicity profile. METHODS: : All patients with craniopharyngiomas consecutively treated between 1999 and 2014 were included. A treatment decision in favor of microsurgery or stereotactic treatment was made interdisciplinarily. For stereotactic drainage, a catheter was implanted, allowing both permanent upstream (into ventricular spaces) and downstream (into prepontine cistern) drainage. Study endpoints were tumor progression, functional outcome, and treatment toxicity. Functional endocrinological and visual outcome analyses referred to data obtained preoperatively and 6 weeks after treatment. The Kaplan‐Meier method was used for survival analysis. Prognostic factors were obtained from proportional hazard models. RESULTS: : Seventy‐nine patients were included. The distribution of clinical and tumor‐related data was well balanced among patients with solid (n = 35) and cystic (n = 44) tumors and those undergoing microsurgical or stereotactic treatment. Cystic tumors had shorter PFS (5‐year PFS: 53.6% vs 66.8%, P = .10) and needed significantly more therapeutic interventions, which was independent of the initial treatment mode. The endocrinological deterioration rate was high for both solid and cystic tumors after microsurgery (59.4% and 85.7%, respectively), whereas it was significantly lower for cystic tumors undergoing stereotactic treatment (23.1%, P < .001). CONCLUSION: : Stereotactic bidirectional drainage of cystic craniopharyngiomas is effective and provides a better endocrinological outcome than conventional microsurgery.